Self-Regulation and Cognitive Emotion Regulation among Adolescents - Khawar, Rabia; Attia, Syeda; Zulfqar , Asia; Hussain, Samavia (Pakistan Journal of Humanities and Social Sciences, 2023)
The present correlational study aimed to examine the relationship between self-regulation and cognitive emotion regulation strategies in adolescents. A sample of 718 adolescents, comprising both boys and girls, from public and private educational institutes in Faisalabad, was conveniently selected for analysis. The participants completed the Adolescents Self-Regulation Inventory (ASRI) and Cognitive Emotion Regulation Questionnaire (CERQ). A significant but negative relationship with one maladaptive cognitive emotion regulation strategy was identified. Additionally, it was found that long-term self-regulation exhibited a significant relationship with several adaptive cognitive emotion regulation strategies, including refocus on planning, positive refocusing, positive reappraisal, and putting into perspective. The Multiple Regression Analysis further revealed that only long-term self-regulation emerged as a significant predictor of other blame (a maladaptive cognitive emotion regulation strategy) and the aforementioned adaptive cognitive emotion regulation techniques. Notably, short-term self-regulation was identified as a significant negative predictor of positive reappraisal. Gender differences in self-regulation and cognitive emotion regulation strategies were observed through independent sample t-tests. This study contributes valuable insights to the existing literature and holds relevance for school psychologists. Importantly, the findings suggest that mindfulness-based interventions have the potential to enhance cognitive emotion regulation and self-regulation in adolescents, offering a promising avenue for helping them develop essential skills to regulate their emotions and behaviors.